Privatization and Social Relations: Meanings of Women’s Land in the Taiwan’s Modern Indigenous Society - Lin, Chinghsiu (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
Since the 1960’s, Truku people, one of the Austronesian groups in Taiwan, have suffered from loss of lands, arising from various governmental policies, privatization of land ownership, and implications of the modern legal system. This paper is to look at how the emergence of the privatization has significantly produced and reproduced various kinds of the gender tensions arising from the conflicts of the women’s land ownership in Truku society. The privatization of the land ownership and the introduction of the modern legal system is argued to have created two unique concepts of land rights: men’s and women’s land in the contemporary Truku society. The former is based on the discourse of the Truku tradition interpreted and represented by the men; but the later one is relied on the legal protection from the modern law for the women and their contributions to farming and taking care of their parents’ lands. Furthermore, the different perspectives of whether or not women customarily or legally have land ownership have profoundly influenced on the social interactions among households in people’s daily lives as well as on the strategies of the land reclamation movements in Truku society.